Challenges for determining frequency of high flow spells for varying thresholds in environmental flows programmes. Issue 1 (2nd January 2017) - Kaur, Simranjit; Horne, Avril; Stewardson, Michael J.; Nathan, Rory; Costa, Alysson M.; Szemis, Joanna M.; Webb, J. Angus
ABSTRACT: High flow spells (or "pulses") are important flow components providing ecological triggers and connectivity in rivers. While the ecological importance of flow spells is well-recognized, the link between ecosystem processes and statistical methods used to define flow spells occurrence has received little attention. Commonly, a spell is defined as an event that exceeds a threshold for a minimum number of consecutive days; however, such arbitrary metrics may be ecologically irrelevant. For example, the ecological value of a sustained high flow spell may be unaffected by a brief period in which flows fall just below the nominated threshold. The inclusion of an independence criterion has the potential to better characterize the ecological relevance of spell metrics, but it introduces the additional problem of how best to define "independence". Existing techniques present inconsistencies in the number of spells identified as the thresholds vary, and this becomes more apparent when characterizing streamflow behaviour over shorter planning periods. This paper presents a new spell metric that resolves the identified inconsistencies and ensures that the number of high flow spells of varying duration varies in a monotonic manner with the threshold. We retain the usual conceptual basis of high flow spells, but adopt an independence criterion that facilitates their characterization for operational purposes, which is more relevant to ecological functions. The simplicity of the approach allows easy incorporation in decision support tools where identifying high flow spells plays a critical role in making important decisions.